2021
DOI: 10.3389/fneur.2021.637620
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Clinical Outcomes to Evaluate the Efficacy of a Multidisciplinary Intervention on Functional Mobility in Parkinson's Disease

Abstract: Introduction: Functional mobility (FM) is a concept that incorporates the capacity of a person to move independently and safely to accomplish tasks. It has been proposed as a Parkinson's disease (PD) functional and global health outcome. In this study, we aimed to identify which kinematic and clinical outcomes changes better predict FM changes when PD patients are submitted to a specialized multidisciplinary program.Methods: PD patients engaged in a pre-defined specialized multidisciplinary program were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(66 reference statements)
1
6
0
Order By: Relevance
“…Possibly, the amplitude-oriented treatments during PD-MCT, i.e., LSVT-BIG exercises [61] additionally contribute to effects on stride length. Similar favorable effects of inpatient multidisciplinary interventions on gait parameters have been reported in observational [99,102] and controlled [103] studies. They likewise demonstrated improvements of gait velocity [99,102,103] and stride [103] or step [102] length measured by wearable digital devices [102], optoelectronic systems [103], and stopwatches [99] after more [102] or similarly intense [99,103] interventions with different [102,103] or similar [99] durations.…”
Section: Changes In Device-based and Clinical Parameterssupporting
confidence: 80%
See 2 more Smart Citations
“…Possibly, the amplitude-oriented treatments during PD-MCT, i.e., LSVT-BIG exercises [61] additionally contribute to effects on stride length. Similar favorable effects of inpatient multidisciplinary interventions on gait parameters have been reported in observational [99,102] and controlled [103] studies. They likewise demonstrated improvements of gait velocity [99,102,103] and stride [103] or step [102] length measured by wearable digital devices [102], optoelectronic systems [103], and stopwatches [99] after more [102] or similarly intense [99,103] interventions with different [102,103] or similar [99] durations.…”
Section: Changes In Device-based and Clinical Parameterssupporting
confidence: 80%
“…Evidence suggests that enhanced executive functions can be associated with dopaminergic [ 105 ] and exercise-related [ 106 , 107 ] effects, might contribute to improvements in gait [ 108 ] and balance [ 109 ], and are, therefore, favorable for daily functioning and quality of life [ 110 ]. Interestingly, an observational study [ 102 ] showed that changes in supervised step length and in dual-task walking abilities under supervised conditions best-predicted changes in functional mobility after a more intense inpatient multidisciplinary intervention [ 102 ]. Crucially, whatever the reasons are for the lack of significant improvement in gait speed and stride length during single-task walking, we argue that the improvement of gait under dual-task conditions is particularly relevant to daily life [ 85 ] and may enhance mobility and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first challenge in gait analysis in free-living environments is that of automatically identifying gait (and non-gait) instances [ 3 ]. Recognising gait in free-living environments enables the calculation of macro and micro features—e.g., step variability and asymmetry [ 4 , 5 ]. The impact of classifying gait in free-living environments is severe to these endpoints, as the misclassification of a set of windows is likely to have a large effect on those micro characteristics and their interpretation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This change of paradigm promises fine-grained monitoring of chronic and neurodegenerative diseases, early prediction of health conditions, accessible self-management, and the enablement of more effective personalised interventions. Recent research shows us the potential of these ubiquitous technologies: with body-worn accelerometer sensors, it is possible to monitor disease fluctuations in free-living environments [1,2,6,17]; predict hospital readmission [11]; monitor depression via social media posts [5]; detect continuous exposure to stress with wrist-worn devices [7]; use smartphones to passively monitor diseases [9,16] or perform rapid tests in low-resource settings [15]; among many others.…”
Section: Introductionmentioning
confidence: 99%